Developmental Responses to Structured Training Loads in Competitive Youth Judo - Vansh Julka; Anulekha Dey (Recent Trends in Sports, 2026)
This study investigates the influence of a planned and regulated training-load structure on the physical and technical growth of elite youth Judoka aged 10 to 16. A four-week training program progressively modified the key variables of training intensity, frequency, and volume to support performance development while avoiding over-fatigue and injury. Ten athletes participated with performance assessed before and after training using tests for Muscular endurance, Core stability, Lower body explosive power, Uchikomi execution speed, Grip strength, Qualitative ratings of Tachi-waza and Ne-waza skills. The post-training data showed improvement across every measured indicator, confirming positive adaptations in strength, power, movement efficiency, and technical execution. Athletes at all experience levels, from those with higher baseline scores to those with lower initial values, showed meaningful enhancement, demonstrating the benefit of systematic load control. The results emphasize that well-designed, age-appropriate training-load management promotes safe, sustainable development while boosting performance in youth Judo athletes. Athletes who entered the program with higher baseline scores, such as participants B and H continued to display improvement, indicating that the training plan was challenging enough to stimulate adaptation even among more experienced Judoka. At the same time, athletes who started with comparatively lower baseline values, such as D and I also showed marked enhancements in performance.
Keywords: Age-appropriate training; elite judoka; movement efficiency; ne-waza; physical development; progressive overload; psychomotor development; randori; skill acquisition; technical development